Peningkatan Kemampuan Membaca Permulaan Melalui Media Flash Card pada Anak Kelompok A RA Al-Huda Gemuntur - Susi Farida; Agus Fathoni Prasetyo (Institut Agama Islam Nahdlatul Ulama Tuban, 2021)
This study aims to improve the ability to read beginning through flash card media in group A children RA Al-Huda Gemuntur. This research uses classroom action research with a quantitative descriptive approach. The research subjects were children of group A RA Al-Huda Senori Merakurak Tuban. In this study, data collection techniques consisted of non-test techniques and test techniques. Non-test techniques, namely through interviews, questionnaires, and documentation. Then the test technique, namely determining the test grid and assessment indicators. Whereas for data analysis techniques, using qualitative data analysis techniques in the form of interviews and questionnaires, and quantitative data analysis techniques in the form of individual and class completeness. The results of the pre-cycle research, there were 4 children (17.3%) who completed learning. In Cycle I, it increased to 11 children (47.8%). Cycle II also experienced a significant increase to 21 children (91.3%). From these results it is evident that through the media flash card can improve the ability to read at the beginning of the group A RA Al-Huda Gemuntur.